Decoding the elite soccer player’s psychological profile - Leonardo Bonetti; Torbjörn Vestberg; Reza Jafari; Debora Seghezzi; Martin Ingvar; Morten L. Kringelbach; Alberto Filgueiras; Predrag Petrovic (Proceedings of the National Academy of Sciences, 2025)
Soccer is arguably the most widely followed sport worldwide, and many dream of becoming soccer players. However, only a few manage to achieve this dream, which has cast a significant spotlight on elite soccer players who possess exceptional skills to rise above the rest. Originally, such attention was focused on their great physical abilities. However, recently, a new perspective has emerged, suggesting that being an elite soccer player requires a deep understanding of the game, rapid information processing, and decision-making. This growing attention has led to several studies suggesting higher executive functions in soccer players compared to the general population. Unfortunately, these studies often had small and nonelite samples, focusing mainly on executive functions alone without employing advanced machine learning techniques. In this study, we used artificial neural networks to comprehensively investigate the personality traits and cognitive abilities of a sample of 328 participants, including 204 elite soccer players from the top teams in Brazil and Sweden. Our findings indicate that elite soccer players demonstrate heightened planning and memory capacities, enhanced executive functions, especially cognitive flexibility, elevated levels of conscientiousness, extraversion, and openness to experience, coupled with reduced neuroticism and agreeableness. This research provides insights into the psychology of elite soccer players, holding significance for talent identification, development strategies in soccer, and understanding the psychological traits and cognitive abilities linked to success.